Development of Monopoly Media in Zhongguo Lvyou Course, Mandarin Language Education Study Program, Semarang State University - Risma Aprilia Widodo; Anggraeni Anggraeni; Lispridona Diner; Dian Yuni Pamuji (Universitas Negeri Semarang, 2023)
The course is a course that aims to increase knowledge about tourist attractions in China. Learning activities for the course use learning media such as powerpoint presentations and textbook summaries, it is known that this does not attract students interest in learning. Based on this, the researcher decided to develop learning media, especially monopoly game learning media in the course so that it attracts more students' interest in learning activities. The aims of this study were (1) to describe the needs of lecturers and students for Monopoly game learning media in the course of the Chinese Language Education Study Program, Semarang State University. (2) Describe the procedure for developing Monopoly game media in the course, Mandarin Language Education Study Program, Semarang State University. (3) Describe the results of expert validation of the Monopoly game media in the course of the Chinese Language Education Study Program, Semarang State University. The research method used is the R and D (Research and Development) research method, namely through 5 stages: (1) Potential Problems, (2) Data Collection, (3) Product Design, (4) Design Validation (5) Design Revision. The results of the validation by material experts showed that the monopoly game learning media in the course of the Semarang State University Mandarin Education Study Program received an overall average score of 86.9, which means that the media is very suitable for use in learning. The results of validation by media experts showed that the monopoly game learning media in the course of the Semarang State University Mandarin Education Study Program received a score of 85.1, which means that the media is suitable for use in learning.